Environmental nanoparticles are significantly over-expressed in acute myeloid leukemia. (November 2016) - Visani, G.; Manti, A.; Valentini, L.; Canonico, B.; Loscocco, F.; Isidori, A.; Gabucci, E.; Gobbi, P.; Montanari, S.; Rocchi, M.; Papa, S.; Gatti, A.M.
Highlights: Increase in AML incidence suggest a possible environmental etiology. PM-derived nanoparticles are linked to blood components in AML patients. PM-derived nanoparticles are almost absent in matched healthy controls. The aggregates of nanoparticles generate protein "corona" with plasma proteins around cells. The protein "corona" generation could transform normal precursor into AML blasts. Abstract: The increase in the incidence of acute myeloid leukemia (AML) may suggest a possible environmental etiology. PM2.5 was declared by IARC a Class I carcinogen. No report has focused on particulate environmental pollution together with AML. The study investigated the presence and composition of particulate matter in blood with a Scanning Electron Microscope coupled with an Energy Dispersive Spectroscope, a sensor capable of identifying the composition of foreign bodies. 38 peripheral blood samples, 19 AML cases and 19 healthy controls, were analyzed. A significant overload of particulate matter-derived nanoparticles linked or aggregated to blood components was found in AML patients, while almost absent in matched healthy controls. Two-tailed Student's t -test, MANOVA and Principal Component Analysis indicated that the total numbers of aggregates and particles were statistically different between cases and controls (MANOVA, P < 0.001 and P = 0.009 respectively). The particles detected showed to contain highly-reactive, non-biocompatible and non-biodegradable metals; in particular, micro- and nano-sized particles grouped in organic/inorganic clusters, with statistically higher frequency of a subgroup of elements in AML samples. The demonstration, for the first time, of an overload of nanoparticles linked to blood components in AML patients could be the basis for a possible, novel pathogenetic mechanism for AML development.